Biodegradation of a vegetable oil based polyurethane and wood flour composites - Aranguren, Mirta Ines (2012)
The biodegradation of a new tung oil based polyurethane and a derived wood flour (WF) composite was followed during 383 days of exposure to soil or vermiculite media. The hydrolytic degradation was the most important mechanism of deterioration in all cases. A shift of the glass transition towards higher temperatures was observed, which was explained as the result of the preferential attack and removal of free or dangling-pendant chains that plasticize the original material. The contact angle of water was observed to decrease with exposure to soil and vermiculite media, denoting changes in the surface of the material that increased its polarity. Simultaneously, changes in color and fracture surfaces were also evident.